FRI0117 Tocilizumab use directly after sdmard failure shows higher response rates and a longer treatment duration. (12th June 2018) - Behrens, F.; Biewer, W.A.; Burmester, G.-R.; Feuchtenberger, M.; Flacke, J.-P.; Hofmann, M.; Kästner, P.; Kellner, H.; Klopsch, T.; Kühne, C.; Tony, H.-P.; Amberger, C.
Abstract : Background: The non-interventional study (NIS) ARATA (NCT02251860 ) observes the clinical effectiveness and safety of subcutaneous Tocilizumab (TCZ) s.c. treatment under routine conditions over a 2 year period. Objectives: In this interim analysis, the patients were subgrouped according to their pretreatment: (I) pretreated exclusively with sDMARD or (II) also pretreated with bDMARD. Methods: TCZ-naive patients (Pts) (≥18 years) with RA, who receive TCZ s.c. treatment, could be included in the study since 2014. Demographic and disease-specific characteristics, the progression of the disease (rheumatoid activity scores), concomitant medications, adverse events (AE) and patient questionnaires were documented. Results: In this interim analysis (reporting date 01-FEB-2017), the data of 912 Pts were evaluated. 319 Pts (35%) were pretreated exclusively with sDMARD and 585 Pts (64.8%) were also pretreated with bDMARD. The main reason for a switch to TCZ s.c. was lacking effectiveness of the pretreatment. In comparison, patients exclusively pretreated with sDMARD demonstrated a shorter median disease duration (6 vs. 9 years), TCZ s.c. was applied at BL more rarely in combination with MTX (23.5% vs. 35.6%) and more rarely with glucocorticoids (59.2% vs. 69.5%). The comorbidity rates were comparable in both groups. However, patients exclusively pretreated with sDMARD suffered half as often from osteoporosis (9.1% vs. 21.2%). Patients Exclusively pretreated with sDMARD had a longer median treatment duration (380.5 vs. 341.0 days) and a higher retention rate to week 52 (78.9% vs. 70.5%). The effectiveness of the TCZ s.c. treatment was examined with 831 patients. More patients with exclusively sDMARD pretreatment achieved a DAS28 remission and remained in remission (figure 1). The change from BL for the CDAI and Dcrit response was higher in the sDMARD subgroup. No new safety signals and no differences between the subgroups for all safety parameters were observed. Conclusions: The results of the third interim analysis of the NIS ARATA confirm the efficacy of TCZ s.c. observed in the approval trials in clinical practice. A fast and effective reduction of disease activity in the treated RA patients as well as a lasting improvement in all RA progression parameters collected was observed. In case of the earlier application of TCZ s.c., directly after sDMARD failure, higher response rates and a longer retention of the treatment were observed. Disclosure of Interest: F. Behrens Grant/research support from: Abbvie, Pfizer, Roche, Chugai, Janssen, Novartis, Consultant for: Abbvie, Pfizer, Roche, Chugai, UCB, BMS, Celgene, MSD, Novartis, Biotest, Janssen, Genzyme, Lilly, Boehringer, Sandoz, W. A. Biewer: None declared, G.-R. Burmester Consultant for: Lilly, Pfizer, Sanofi, Roche, M. Feuchtenberger Consultant for: MSD, Roche, Abbvie, Chugai, Pfizer, UCB, J.-P. Flacke Employee of: Roche Pharma AG, M. Hofmann Employee of: Chugai Pharma Europe Ltd., P. Kästner: None declared, H. Kellner Consultant for: Roche, T. Klopsch: None declared, C. Kühne Consultant for: Celgene, Roche, Pfizer, Novartis, BMS, H.-P. Tony Consultant for: Roche Pharma, Abbvie, BMS, Chugai, Janssen, Novartis, Sanofi, Lilly, Speakers bureau: Roche Pharma, Abbvie, BMS, Chugai, Janssen, Novartis, Sanofi, Lilly, C. Amberger Consultant for: Chugai, AbbVie, Celgene, MSD, Pfizer, BMS, HexaL